The relationship between animal welfare and economic performance at farm level: A quantitative study of Danish pig producers - Arne Henningsen; Tomasz Gerard Czekaj; Björn Forkman; Mogens Lund; Aske Schou Nielsen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2016)
We propose a theoretical framework for the relationship between animal welfare and the economic performance of livestock farms. We empirically analyse this relationship based on a unique data set of randomly sampled Danish pig herds that includes information from unannounced inspections of the compliance with the animal welfare legislation. We find large variations in economic performance indicators and animal welfare indicators. The relationship between these two indicators is rather weak, but tends to be slightly positive. We conclude that management has a major influence on both economic performance and animal welfare so that good farm managers are able to obey all animal welfare regulations and, at the same time, achieve a high economic performance.
Keywords: Q12; 330; animal welfare; gross margin; technical efficiency; pig farms; Denmark